2021
DOI: 10.1126/science.abf6505
|View full text |Cite
|
Sign up to set email alerts
|

Early origin of sweet perception in the songbird radiation

Abstract: Early events in the evolutionary history of a clade can shape the sensory systems of descendant lineages. Although the avian ancestor may not have had a sweet receptor, the widespread incidence of nectar-feeding birds suggests multiple acquisitions of sugar detection. In this study, we identify a single early sensory shift of the umami receptor (the T1R1-T1R3 heterodimer) that conferred sweet-sensing abilities in songbirds, a large evolutionary radiation containing nearly half of all living birds. We demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 64 publications
0
26
0
Order By: Relevance
“…This combination of critical domains represents an interesting example of convergence with the independent acquisition of sweet taste seen in the songbird radiation: in addition to the modifications we have described to distinct ligand-binding domains (T1R3 in hummingbirds and T1R1 in songbirds), we now show that the CRD-TMD region of the opposite paralog (T1R1 in hummingbirds; fig. 2 c–d , T1R3 in songbirds; Toda et al 2021b ) also plays a critical role in both radiations. Each acquisition of carbohydrate and sweetener detection therefore requires modifying a combination of both domains, but hummingbirds and songbirds recruit alternate paralogs in a mirror-image fashion ( fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This combination of critical domains represents an interesting example of convergence with the independent acquisition of sweet taste seen in the songbird radiation: in addition to the modifications we have described to distinct ligand-binding domains (T1R3 in hummingbirds and T1R1 in songbirds), we now show that the CRD-TMD region of the opposite paralog (T1R1 in hummingbirds; fig. 2 c–d , T1R3 in songbirds; Toda et al 2021b ) also plays a critical role in both radiations. Each acquisition of carbohydrate and sweetener detection therefore requires modifying a combination of both domains, but hummingbirds and songbirds recruit alternate paralogs in a mirror-image fashion ( fig.…”
Section: Resultsmentioning
confidence: 99%
“…The savory, or umami, receptor of vertebrates is a heterodimer composed of two G-protein coupled receptors, T1R1 and T1R3. In hummingbirds and in songbirds, the T1R1–T1R3 receptor, ancestrally responsive likely only to amino acids ( Nelson et al 2002 ; Baldwin et al 2014 ), has convergently undergone a functional shift, enabling these species to detect sugars ( Baldwin et al 2014 ; Toda et al 2021b ). A common way that novel functions emerge is through gene duplication and neofunctionalization of one duplicate, which can permit the ancestral function to be retained ( Innan and Kondrashov 2010 ); in avian sugar sensing, however, a single receptor may be responsible for detecting both sugars and amino acids, potentially requiring a trade-off.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More broadly, sequencing and assembling a genome from a nectivorous tanager adds to the collection of obligate nectivores sequenced among the vertebrate Tree of Life ( Feng et al 2020 ; Supplementary Table S2), providing another avenue of research into the genetic basis of adaptations common to a nectivorous lifestyle, including: sweet taste perception ( e.g. , Baldwin et al 2014; Toda et al 2021 ), sugar metabolism ( e.g. , Schondube and Del Rio 2004; Workman et al 2018), spatial memory of floral resources ( e.g.…”
Section: Resultsmentioning
confidence: 99%
“…These molecular interaction sites or regulatory sites at protein surfaces can be hotspots of protein adaptation. Indeed, some specific molecular interactions have been linked to adaptive evolution in several case studies ( Hughes and Nei 1988 ; Bachtrog 2008 ; Schott et al 2014 ; Levin and Malik 2017 ), a recent study on sweet taste receptors in the songbird radiation ( Toda et al 2021 ), and large-scale studies based on proteins with high-quality structural models ( Slodkowicz and Goldman 2020 ). In the latter study, the authors showed that amino acids under positive selection in mammals tend to cluster closer to binding sites of exogenous ligands than expected by chance ( Slodkowicz and Goldman 2020 ), suggesting an important role of functionally important regions in adaptive evolution.…”
Section: Discussionmentioning
confidence: 99%